1999
DOI: 10.1007/s004420050836
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and sublethal costs of autotomy and predator presence in damselfly larvae

Abstract: We studied the costs of lamellae autotomy with respect to growth and survival of Lestes sponsa damselfly larvae in field experiments. We manipulated predation risk by Aeshna cyanea dragonfly larvae and lamellae status of L. sponsa larvae in field enclosures and compared differences in numbers, size and mass of survivors among treatments. In the absence of a free-ranging A. cyanea larva, about 29% of the L. sponsa larvae died. This was probably due to cannibalism. The presence of a free-ranging A. cyanea reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 41 publications
1
29
1
Order By: Relevance
“…Studies on damselflies have found no effect of thinning but an effect related to reduction in feeding behaviour, which caused a reduced growth effect (McPeek 1990(McPeek , 1998Stoks et al 1999). These studies differ from ours in two respects.…”
Section: Discussioncontrasting
confidence: 69%
“…Studies on damselflies have found no effect of thinning but an effect related to reduction in feeding behaviour, which caused a reduced growth effect (McPeek 1990(McPeek , 1998Stoks et al 1999). These studies differ from ours in two respects.…”
Section: Discussioncontrasting
confidence: 69%
“…The presence of a caged predator had similar life history effects as a low food level. Such predator-induced effects have previously been demonstrated in this study species (Stoks et al 1999a(Stoks et al , 1999b and in many other taxa (e.g. Skelly and Werner 1990;Feltmate and Williams 1991;Peckarsky et al 1993;Ball and Baker 1996;McPeek 1998).…”
Section: Effects On Life Historymentioning
confidence: 84%
“…Directly after their moult into instar F-1, larvae were placed under the experimental conditions. I exposed the damselflies to the presence of Aeshna cyanea dragonfly larvae because they are important predators of L. sponsa (Stoks et al 1999a(Stoks et al , 1999b. Dragonfly larvae (instar F-2) were collected from the same pond and housed separately in the laboratory under the same conditions as the L. sponsa larvae and fed ad libitum with Chironomus larvae.…”
Section: Study Speciesmentioning
confidence: 99%
“…Given its cytotoxicity, activated PO loses its activity rapidly, and to maintain constant levels there is a need for continuous production (Sugumaran 2002 (Stoks 1999(Stoks , 2001Stoks et al 1999). The decreased PO activity after 24 hours was not due to a decrease in overall protein synthesis rate as lamellae autotomy did not affect RNA/DNA ratios (see appendix in the electronic supplementary material).…”
Section: Discussionmentioning
confidence: 99%
“…When larvae reached the final instar, we removed all three lamellae from one random half of the larvae by gently pulling them with two fingers until the animals autotomized these appendages at the specialized breaking joints (as in Stoks 1999;Stoks et al 1999). The other half of the larvae underwent a sham operation without removing the lamellae.…”
Section: Methodsmentioning
confidence: 99%